Arsenic stress in plants: A metabolomic perspective - José Isabel Martínez-Castillo; Adriana Saldaña-Robles; César Ozuna (Plant Stress, 2022)
Arsenic (As) is a natural contaminant that exists naturally in the earth crust and it is toxic to plant cells. Studies involving the absorption of As by plants have already been described previously. Recently, researchers have intended to understand the molecular and physiological mechanisms that intervene and interact in As absorption. The study of the metabolome in plants under As stress makes use of advances in instrumentation and analytical equipment that allows for metabolomics to be performed. The aim of this comprehensive review is to provide a revision of metabolomic studies related to As-induced stress in plants and the main alterations in its metabolism compared to a non-stress situation. According to the reviewed research, As affects both primary and secondary metabolism, with amino acids, proteins, and the antioxidant complex enzymes being the molecules most studied and related to As stress. However, non-enzymatic compounds, derived from the secondary metabolism, have been scarcely studied in metabolomic studies on As-induced stress in plants. In conclusion, metabolomics as a research approach to studying As stress in plants could permit in-depth understanding of As-related behavior in the plant metabolism